Peningkatkan Kemampuan Kognitif Fisika Melalui Implementasi Model Pembelajaran Investigasi Kelompok - Siti Aisah Sitanggang; Yenni Khairani Lubis (Gravity Journal, 2025)
This study aims to analyze the effectiveness of the group investigation learning model in improving students' cognitive learning outcomes in Physics at SMA Negeri 1 Kotapinang. This study uses a Classroom Action Approach with mixed methods. A quantitative approach is used to measure the improvement in students' cognitive learning outcomes using value data processed with SPSS 26 (including validity, reliability, difficulty, and question discrimination tests). Meanwhile, a qualitative approach is used to analyze teacher and student activities during learning through direct observation and interviews. The value of students' cognitive abilities before the study only reached 30% of the total. Then after the implementation of cycle 1 meeting 1 the percentage of completion increased to 42%. Continued at meeting II to 64%. Because it has not reached the success indicator, it is continued to cycle 2 where in meeting I the percentage of completion increased to 69% and continued to meeting II with a percentage of completion of 80%. Because it has reached the success indicator, the cycle can be ended. In conclusion, this study has succeeded in improving physics cognitive abilities in the parabolic motion material at SMA Negeri 1 Kotapinang.